2019
DOI: 10.1093/jee/toz199
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Plant Flavonoids Increase Whitefly Resistance and Reduce Spread of Tomato yellow leaf curl virus

Abstract: Tomato yellow leaf curl virus (TYLCV), a begomovirus (genus Begomovirus) is the causal agent of tomato yellow leaf curl disease (TYLCD), which causes severe damage to tomato (Solanum lycopersicum) crops throughout tropical and subtropical regions of the world. TYLCV is transmitted by the whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) in a circulative and persistent manner. Our previous studies showed that tomato flavonoids deter B. tabaci oviposition, but the effects of tomato flavonoids on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 49 publications
1
43
0
Order By: Relevance
“…To investigate whether T. urticae infestation affects the levels of leaf flavonoids, which function as a resistance factor against whiteflies and TYLCV transmission (Su et al, ; Yao et al, ), we compared flavonoids levels in tomato plants with and without T. urticae . The total flavonoid levels did not differ significantly between tomato plants with and without T. urticae ( F 1,14 = 3.389, p = .087; Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether T. urticae infestation affects the levels of leaf flavonoids, which function as a resistance factor against whiteflies and TYLCV transmission (Su et al, ; Yao et al, ), we compared flavonoids levels in tomato plants with and without T. urticae . The total flavonoid levels did not differ significantly between tomato plants with and without T. urticae ( F 1,14 = 3.389, p = .087; Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a recent study showed that B. tabaci infestation changed tomato flavonoid metabolism and thereby enhanced susceptibility to conspecifics and induced conspecific feeders to aggregate on the host plant (Su et al, ). Additionally, they also suggested that flavonoids can deter B. tabaci feeding and reduce its transmission of TYLCV (Yao et al, ); more specifically, high flavonoid levels in tomato deterred B. tabaci probing and salivating, and therefore reduced the transmission of TYLCV. Third, B. tabaci regularly infests tomato plants with co‐occurring T. urticae , especially when plants are infected with TYLCV (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Host plant resistance to insect vectors is also one of the best strategies to manage circulative vector-borne virus diseases [22]. An advantage can then be gained from host plant resistance as an effective means to control whitefly infestations [23,24] which might help to reduce also incidence of transmitted viruses as demonstrated for the whitefly Bemisia tabaci Gennadius [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Plant DNA was extracted with a Plant Genomic DNA Kit (Tiangen Biotech, Beijing, China), and the TYLCV infection status of the tissue was determined by PCR amplification of a TYLCV DNA fragment (~410 bp) using the specific primers listed in Table S1. Virus titre was quantified by quantitative PCR (qPCR) on an ABI 7500 real‐time PCR system (Applied Biosystems, Foster City, CA) with SYBR Green PCR Master Mix (TaKaRa, Dalian, China) using the specific qPCR primers listed in Table S1 and according to previously described methods (Yao et al, 2019). The relative TYLCV titres in plants were normalized with the internal reference gene encoding 25S ribosomal RNA from tomato.…”
Section: Methodsmentioning
confidence: 99%
“…(proteinase inhibitor II) and POX (peroxidase) (Gorovits et al, 2007;McKenzie et al, 2002;Sahu et al, 2010). Because tomato flavonoids, a group of important secondary metabolites, were known to reduce TYLCV transmission by whiteflies (Su et al, 2020;Yao et al, 2019), we also analysed the expression of two genes involved in flavonoid biosynthesis: CHS (chalcone synthase) and FLS (flavonol synthase).…”
Section: Z-3-hol Triggers Tomato Plant For Enhanced Immunity Againsmentioning
confidence: 99%